(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents a concept of an extended iBeacon system for proximity target marketing. iBeacon is a proximal wireless notification service proposed by Apple, Inc. This service uses beacon modules emitting radio waves based on Bluetooth Low Energy technology and provides automatic triggering of a single notification from a beacon module to multiple smart phones at proximity. In usual iBeacon systems, there is one-to-one correspondence between notification and beacon module. However, if we introduce a memory to remember the history of iBeacon detection, iBeacon systems can be extended to handle multiple notifications by multiple beacon modules with awareness of some contexts of pedestrians’ moving directions, which enables a guide, for example, to the exit of buildings. We explain this idea for proximity target marketing using iBeacon and discuss its implementation with our simple experiment and performance evaluation. We are going to explain what it is and how it works, in order to understand how the app works and how it uses these potentialities. This new technology may also be used by Android system. iBeacon works with Bluetooth Low Energy (BLE), also known as Bluetooth 4.0 or intelligent Bluetooth. We show in this project how iBeacon technically really work, The app. Smart devices, such as Android phone can detect advertising signals sent by the low energy consumption tiny device. Notifications will be pushed automatically to the user when smart device with iBeacon Apps come to certain areas. It provides promising and portfolio usage scenarios for business, such as retail stores, to push related information about customers’ interested items with the awareness of customers’ location.